Signal Transduction Pathways Involved in Acupuncture-Mediated Inhibition of Synovitis in Knee Osteoarthritis: A Comprehensive Review - Cao Q; Li Y (International Journal of General Medicine)
Qingxi Cao, Yuehua Li Department of Sports Medicine, The People’s Hospital of Baoan Shenzhen, Shenzhen, Guangdong Province, People’s Republic of ChinaCorrespondence: Yuehua Li, Department of Sports Medicine, The People’s Hospital of Baoan Shenzhen, Shenzhen, Guangdong Province, 518100, People’s Republic of China, Tel +13560331881, Email 18525428109@163.comAbstract: Knee osteoarthritis (KOA) is a prevalent degenerative joint disorder characterized by synovitis, cartilage degradation, and nociception, in which dysregulated immune responses and excessive pro‑inflammatory mediators drive synovial inflammation as a central pathogenic mechanism. Acupuncture, a cornerstone of traditional Chinese medicine, has demonstrated clinical efficacy in alleviating pain, attenuating synovial pathology, and restoring joint function in KOA. In this review, we systematically elucidate the molecular mechanisms by which acupuncture suppresses synovial inflammation, focusing on its multimodal modulation of five critical signaling cascades: norepinephrine (NE) signaling, the TLRs/NF‑κB pathway, the MCP1/CCR2 axis, the NLRP3 inflammasome, and the Ras‑Raf‑MEK1/2‑ERK1/2 pathway. Relevant studies published between 2000 and 2024 were identified through comprehensive searches of PubMed and CNKI using terms such as “acupuncture + synovitis + MAPK pathway”, “acupuncture + inflammation”, and “knee osteoarthritis + molecular mechanisms”. English and Chinese peer‑reviewed articles reporting preclinical or clinical data on acupuncture’s effects in KOA synovitis were included, while studies lacking mechanistic insights or unrelated to synovial inflammation were excluded. Study validity, risk of bias, and methodological rigor were appraised using the GRADE framework. Cumulative evidence indicates that acupuncture exerts anti‑inflammatory and chondroprotective effects by orchestrating multi‑pathway regulation, thereby reducing inflammatory mediators, promoting tissue repair, and improving joint function. As a promising adjunct to pharmacotherapy—particularly in early‑stage KOA—acupuncture merits further validation through large‑scale clinical trials aimed at optimizing treatment parameters, confirming long‑term efficacy, and exploring synergistic combinations with emerging therapies to enable personalized KOA management.Keywords: knee osteoarthritis, synovial inflammation, acupuncture, signaling pathway